Recovery at 30: Integrating Lived Experience Expertise into Mental Health Research in Israel - Alfia-Burstein, Shira; Oren, Avi; Goldfarb, Yael; Stengar-Elran, Renana; Pinfold, Vanessa; Roe, David; Moran, Galia S. (Community mental health journal, 2025)
A major component of recovery is the inclusion of lived experience to transform the culture of Mental Health (MH) services. In Israel lived experience has been increasingly integrated into services through peer roles. However, lived experience knowledge and expertise has not been sufficiently nor systematically integrated into the design of mental health research. This paper documents an attempt to initiate change by convening multiple stakeholders (with and without lived experience) in a specialized workshop aiming to learn and discuss the potential role of lived experience for mental health research in Israel. Participants raised ideas and core questions on how lived experience can shape research and augment mental health practices and policies. They highlighted current challenges regarding self-disclosure facing lived experience researchers, as well as challenges for developing participatory research collaborations among consumers, family members and practitioners. By bringing to the fore-front the ‘insider perspective’ of MH system as experienced among service users and families, we expect a development of a research culture with reduced paternalism, increased coproduction and recovery-orientation. We hope this endeavor will inspire others and help develop a lived experience expertise-based research network of interested stakeholders.